Applicability of the chromium reducible sulfur test for acid metalliferous drainage prediction in hard rock mining. (April 2018) - Black, Silvia; Allen, David; North, Michael; Price, Barry; Rothnie, Neil; Sharma, Rajesh
Abstract: The potential for Acid and Metalliferous Drainage (AMD) from waste rock in mining operations is a key issue which must be addressed at all stages, from the initial mining proposal to rehabilitation and site closure. The Chromium Reducible Sulfur (CRS) method was originally introduced into Australia as a rapid and cost-effective method to estimate the acid production potential of acid sulfate soils. However, concerns are being raised over its potentially inappropriate use without supporting scientific evidence to assess the AMD potential of mine wastes in hard rock mining, especially those containing base metal (lead, zinc, copper and nickel) sulfides. This paper outlines the results of a comparative laboratory study of 55 Western Australian mine waste samples and mineral specimens for AMD potential using CRS results from routine commercial laboratories normally handling soil samples as well as conventional approaches. CRS was found to be generally suitable for many applications, particularly for common iron sulfides at low to moderate concentrations (relevant to many iron ore, mineral sands and gold mining operations). However, CRS was not a reliable predictor of potential acid production from samples containing elevated concentrations of iron sulfides, base metal sulfides, arsenopyrite or molybdenite. Issues with CRS precision and bias were also indicated. A good understanding of sulfide mineralogy is required for accurate AMD predictions of these types of mine wastes, and cannot be obtained from any single test. Highlights: The CRS method to assess AMD potential has limitations in hard rock applications. CRS variability should be investigated to improve reliability for hard rock. CRS under-reported acid potential for ores containing arsenopyrite and molybdenite. If used, CRS should be combined with NAG testing and mineralogy for AMD prediction.